A Style Manual for Citing Microform and Nonprint Media - Fleischer, Eugene B. (American Library Association, 1978)
Traditionally, researchers are required to acknowledge all sources via citations and bibliographic information. In previous decades, scholars did not have a set standard of rules in order to follow and cite. The American National Standards Institute (ANSI) continues to develop and update a standard for all print and nonprint media to establish consistency. This manual is designed to assist in the writing citations and bibliography research papers and theses in regards to nonprint media with supporting examples.